DISKURSUS FENOMENA HAMIL DI LUAR NIKAH DALAM PERTUNJUKAN WAYANG JOBLAR - Kharisma Pradana, Gede Yoga (E-Jurnal Kajian Budaya (Online Journal of Cultural Studies); Volume 01, Nomor 01, Desember 2012)
Unexpected pregnancy is a story in the performance of Wayang Joblar reflecting a social currently taking place in Denpasar City. As an innovative performance of leather puppets, Wayang Joblar narrates a story that Dewi Trijata is unexpectedly made pregnant by Jembawan who is disguised as Hanoman. It is narrated as the discourse of the phenomenon of unexpected pregnancy and offers a solution to it from the aspects of conformity and responsibility. By observing the text in a deconstructive manner, though the narrative components, it can be understood that the text contains general and particular truths. From the analysis of the phenomenon of the unexpected pregnancy presented in the form of the performance of wayang, it was found that there were three types of ideologies; they are sex ideology, gender ideology, and patriarchal ideology. The discourse of the phenomenon of the unexpected pregnancy presented in the performance of Wayang Joblar functioned as alternative amusement and moral education. The implications were that the established cultural order became torn and that the boundary between the high art and popular one became unclear. However, it could amuse, give solution to the current social problem which could enrich the Wayang Balinese performing art.
Keywords: Unexpected Pregnancy, Wayang Joblar Performance